A survey of evidence-based practice, training, supervision and clinician confidence relating to post-traumatic stress disorder (PTSD) therapies in UK child and adolescent mental health professionals. Issue 1 (31st December 2020) - Finch, Jodie; Ford, Catherine; Lombardo, Chiara; Meiser-Stedman, Richard
ABSTRACT: Background: Post-Traumatic Stress Disorder (PTSD) in children and adolescents has received increasing recognition in recent decades. Despite development of treatments and improved dissemination efforts, research has identified a number of barriers to implementing these approaches. Objective: This study sought to understand what interventions mental health professionals working with children and adolescents utilised to treat PTSD, their training and supervision, their confidence in assessing and treating PTSD, and how these factors relate to clinicians characteristics (e.g. age, gender, professional background). Method: The study comprised an internet-delivered survey of clinicians working in child and adolescent mental health services in the UK (N = 716). Results: Many clinicians (>40%) had not received training in working with PTSD, with considerable variation between professional background. Lack of training and supervision was associated with reduced clinician confidence in treating children with PTSD (possible range 0–10; training M = 7.54, SD = 1.65, no training M = 5.49, SD = 2.29; supervision M = 7.53, SD = 1.63, no supervision M = 5.98, SD = 2.35). Evidence-based therapies for PTSD such as Trauma-Focused Cognitive-Behavioural Therapy and Eye Movement Desensitisation and Reprocessing were only endorsed modestly by clinicians (58.4% and 37.5%, respectively). Regression analyses identified that lack of training and supervision were significant barriers to the use of evidence-based interventions. Other predictors of clinician confidence and use of evidence-based interventions included profession and years of experience. Participants almost universally wanted more training in working with PTSD. Conclusions: Evidence-based treatments are not currently universally delivered by mental health professionals in the UK, with certain professions particularly lacking training and confidence with this condition. Training around trauma and PTSD may be an ongoing need to boost and maintain confidence in working with PTSD in youth.